Evaluation of the Efficacy of 50% Autologous Serum Eye Drops in Different Ocular Surface Pathologies. (22nd July 2014) - Semeraro, Francesco; Forbice, Eliana; Braga, Osvaldo; Bova, Alessandro; Di Salvatore, Attilio; Azzolini, Claudio
Abstract : Purpose . This study evaluated the efficacy of 50% autologous serum eye drops in ocular surface diseases not improved by conventional therapy. Methods . We analyzed two groups: (1) acute eye pathologies (e.g., chemical burns) and (2) chronic eye pathologies (e.g., recurrent corneal erosion, neurotropic keratitis, and keratoconjunctivitis sicca). The patients were treated for surface instability after conventional therapy. The patients received therapy 5 times a day until stabilization of the framework; they then reduced therapy to 3 times a day for at least 3 months. We analyzed the best corrected visual acuity, epithelial defects, inflammation, corneal opacity, and corneal neovascularization. We also analyzed symptoms such as tearing, burning, sense of foreign body or sand, photophobia, blurred vision, and difficulty opening the eyelids. Results . We enrolled 15 eyes in group 1 and 11 eyes in group 2. The average therapy period was 16 ± 5.86 weeks in group 1 and 30.54 ± 20.33 weeks in group 2. The epithelial defects all resolved. Signs and symptoms improved in both groups. In group 2, the defect recurred after the suspension of therapy in 2 (18%) patients; in group 1, no defects recurred. Conclusions . Autologous serum eye drops effectively stabilize and improve signs and symptoms in eyes previously treated with conventional therapy.